Diesel exhaust augments allergen-induced lower airway inflammation in allergic individuals: a controlled human exposure study. Issue 1 (16th November 2015) - Carlsten, Chris; Blomberg, Anders; Pui, Mandy; Sandstrom, Thomas; Wong, Sze Wing; Alexis, Neil; Hirota, Jeremy
Abstract : Rationale: Traffic-related air pollution has been shown to augment allergy and airway disease. However, the enhancement of allergenic effects by diesel exhaust in particular is unproven in vivo in the human lung, and underlying details of this apparent synergy are poorly understood. Objective: To test the hypothesis that a 2 h inhalation of diesel exhaust augments lower airway inflammation and immune cell activation following segmental allergen challenge in atopic subjects. Methods: 18 blinded atopic volunteers were exposed to filtered air or 300 µg PM2.5 /m 3 of diesel exhaust in random fashion. 1 h post-exposure, diluent-controlled segmental allergen challenge was performed; 2 days later, samples from the challenged segments were obtained by bronchoscopic lavage. Samples were analysed for markers and modifiers of allergic inflammation (eosinophils, Th2 cytokines) and adaptive immune cell activation. Mixed effects models with ordinal contrasts compared effects of single and combined exposures on these end points. Results: Diesel exhaust augmented the allergen-induced increase in airway eosinophils, interleukin 5 (IL-5) and eosinophil cationic protein (ECP) and the GSTT1 null genotype was significantly associated with the augmented IL-5 response. Diesel exhaust alone also augmented markers of non-allergic inflammation and monocyte chemotactic protein (MCP)-1 and suppressed activity of macrophages and myeloid dendritic cells. Conclusion: Inhalation of diesel exhaust at environmentally relevant concentrations augments allergen-induced allergic inflammation in the lower airways of atopic individuals and the GSTT1 genotype enhances this response. Allergic individuals are a susceptible population to the deleterious airway effects of diesel exhaust. Trial registration number: NCT01792232.